2020
DOI: 10.1007/s40888-020-00202-8
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of import tariff costs for Italian exporting firms

Abstract: Since production and trade are increasingly organized within global value chains (GVCs), assessing who effectively pays the cost of protection is not straightforward and since productive processes are internationally fragmented, quantifying the effects of trade policy requires an enhanced analytical framework that takes international input–output linkages into account to assess the implications trade costs have on competitiveness at national and sector levels. This paper defines a new synthetic measure of trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Their results showed that the formalization of preferential trade agreements with natural trade partners may pave the way for Brazilian industry to integrate into GVCs. Fusacchia et al (2021) used a CGE model focusing on Italy to explore the impact of tariffs on exporting companies that rely on imported intermediate products in the context of GVC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their results showed that the formalization of preferential trade agreements with natural trade partners may pave the way for Brazilian industry to integrate into GVCs. Fusacchia et al (2021) used a CGE model focusing on Italy to explore the impact of tariffs on exporting companies that rely on imported intermediate products in the context of GVC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This methodology facilitates a comparative analysis of the effects of policy-based GVC. By removing the aforementioned double counting included in the total exports, the method more accurately explains the trade relation [76,77].…”
Section: Brief Description Of the Cge Modelsmentioning
confidence: 99%